Battison thesis 2012 - Battison, L (University of Oxford, 2012)
Files relating to Dr Leila Battison's thesis "Exceptional preservation of cells in phosphate and the early evolution of the biosphere" (2012). Thesis files 1: badachroassemblage.pdf 295 KB badachrolog.pdf 5,520 KB badachromiss.pdf 56,195 KB badachrophos.pdf 20,926 KB balgaylog.pdf 363 KB balgymiss.pdf 46,577 KB basinschematic.pdf 446 KB boulevardphos.pdf 43,087 KB boulevardsed.pdf 39,236 KB brochellog.pdf 1,112 KB brochelmiss.pdf 84,582 KB brochelphos.pdf 28,828 KB cailleachlog.pdf 1,018 KB cailleachphos.pdf 22,991 KB carparkphos.pdf 19,093 KB Thesis files 2: centennialsed.pdf 47,965 KB clayphospres.pdf 12,662 KB clustervscellsize.pdf 499 KB coccoidsize.pdf 248 KB degradationplate.pdf 71,819 KB diabaigassemblage.pdf 499 KB diabaiglog.pdf 564 KB diabaigphos.pdf 28,828 KB diavscailleachassemblage.pdf 765 KB disorderedstructures.pdf 56,724 KB ferrylandphos.pdf 26,197 KB fibsemedx.pdf 2,250 KB fibtem.pdf 7,083 KB filamentdiameters.pdf 320 KB fishfarmassemblage.pdf 491 KB Thesis files 3: fishfarmlog.pdf 479 KB fishfarmmiss.pdf 81,350 KB fishfarmphos.pdf 23,903 KB fladdayassemblage.pdf 490 KB fladdaylog.pdf 399 KB fladdayphos.pdf 22,556 KB frustrationphos.pdf 19,182 KB frustrationsed.pdf 57,499 KB grandbankphos.pdf 22,387 KB gunflintmap.pdf 697 KB gunflintmiss.pdf 97,236 KB gunflinttaphospace.pdf 774 KB heterotrophy.pdf 6,520 KB kylelog.pdf 3,516 KB lacustrine.pdf 36,540 KB Thesis files 4: littledanzigphos.pdf 23,530 KB lowerdiabaigmiss.pdf 107,067 KB matprofiles.pdf 158 KB missformation.pdf 645 KB morphotypes.pdf 30,550 KB newfyfossils.pdf 8,193 KB newfymap.pdf 534 KB newfystrat.pdf 284 KB orderedstructures.pdf 131,250 KB oxlogo.pdf 91 KB passsed.pdf 23,159 KB phosformation.pdf 337 KB phostechniques.pdf 6,152 KB phosvsshaleplots.pdf 241 KB phosvsshaletapho.pdf 1,034 KB Thesis files 5: purevsgranular.pdf 39,669 KB qrcode.pdf 101 KB ramandark.pdf 1,753 KB ramanlight.pdf 2,794 KB rivershorephos.pdf 32,988 KB samples.pdf 422 KB samples1.pdf 257 KB samples2.pdf 220 KB samples3.pdf 241 KB samples4.pdf 248 KB samples5.pdf 262 KB samples6.pdf 219 KB samples7.pdf 218 KB samples8.pdf 208 KB schreibersed.pdf 36,146 KB Thesis files 6: sectionvsmacplots.pdf 258 KB sectionvsmactapho.pdf 1,124 KB sedmodification.pdf 53,017 KB semorphs.pdf 3,850 KB serialfibsem.pdf 5,562 KB shieldaigbaylog.pdf 732 KB shieldaiglog.pdf 237 KB shieldaigmiss.pdf 103,332 KB shieldaigphos.pdf 12,166 KB silosphos.pdf 23,530 KB sleatlog.pdf 806 KB spaniardsphos.pdf 37,424 KB spatialvariation.pdf 298 KB specials.pdf 38,489 KB stratigraphickey.pdf 458 KB Thesis files 7: systematics1.pdf 23,229 KB systematics2.pdf 34,954 KB systematics3.pdf 23,355 KB taphoplate.pdf 21,325 KB timeline.pdf 231 KB torridongeology.pdf 678 KB torridonmicroscopic.pdf 284 KB totalabundance.pdf 214 KB upperdiabaiglog.pdf 782 KB upperdiabaigmiss.pdf 76,430 KB wireframe.pdf 601 KB wrinklemap.pdf 1,030 KB carparksed.jpg 8,031 KB gunflintbasin.jpg 868 KB gunflinttaxa.jpg 12,915 KB microspheres.jpg 9,462 KB phosloci.jpg 277 KB rivershoresed.jpg 9,123 KB roadcutsed.jpg 10,122 KB stromatolites.jpg 18,293 KB